Study of the interfacial properties of heterostructures based on aluminum and hydrogenated diamond - Folegatti, Felippe [UNESP]; Oliveira, Eliezer Fernando [UNESP] (Springer Nature, 2025)
We theoretically investigated composites of diamond and aluminum (Al-D) as well as hydrogenated diamond and aluminum (Al-DH) under different temperature conditions. Our findings reveal the presence of a strong electric dipole at the Al-D interface, directed toward the aluminum side. However, the inner aluminum layers may exhibit a negative net charge. In contrast, for Al-DH, the average net electric charge of the aluminum surface is nearly identical to that of the hydrogen on the diamond surface, leading to an empty space at the Al-DH interface due to electrostatic repulsion.